ANALISIS KELAYAKAN PADA USAHA KOLAM IKAN LELE DUMBO DI DESA PUNTARI MAKMUR KECAMATAN WITA PONDA KABUPATEN MOROWALI - ROSALINA, INTAN (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2018)
This study aims to analyze the feasibility of Dumbo Lele fish business based on the non financial and financial aspects. For the non financial aspect which cover market, technical, managenent, legal, social, economic and enviromental aspects which carried out quantitatively. While, financial aspects can be seen form investment criteria such as: Payback Period, Net Present Value, Internal Rate of Return and Net B/C using quantitative methods which are processed by Microsoft Excel 2007 and presented descriptively. Based on the result of non financial analysis, the business is feasible and can be run continuously. Moreover, the result of financial analysis using the investment criteria shows that the payback period or time needed to return the investment cost is 2 years 5 months 88 days which shorter than the economic life of project, which is 5 years. The Net Present Value value is greater than zero, which is Rp 200,638,462,-, and the Internal Rate of Return is 42.31% greater than discount factor 14.4%. The profit achieved if the cost is Rp 1or the Net B/C value is Rp 1.79 at a discount rate of 14.4%. From the results of the study shows that Lele Dumbo fishing business owned by Mr. Usdar at Puntari Makmur village, Wita Ponda District in Morowali Regency is feasible to be run.